The Impact of Chitosan on Oxidative Stress in Liver of Rats Loaded With Lead Acetate - Ozdek, U; Toz, H; Kömüroğlu, AU; Mis, L; Değer, Y (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was conducted to determine the impact of chitosan on lead (Pb)-induced hepatotoxicity. Thus, lead acetate was administered intraperitoneally (50 mg/kg for 5 days) and chitosan was given as 200 mg/kg via oral gavage for 28 days. When the trial was terminated, it was determined that aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) activities in serum as well as Pb, 8-hydroxy-deoxyguanosine (8-OHdG) and malondialdehyde (MDA) levels and catalase (CAT) activity in liver tissue significantly increased, however reduced glutathione (GSH) and ceruloplasmin (Cp) levels in liver and high density lipoproteins (HDL) in serum had a significant decrease in the Pb group when compared to the control group. The administration of chitosan significantly prevented Pb-induced changes in serum liver enzyme activities, 8-OHdG and MDA levels. In addition, chitosan showed a statistically insignificant effect on reduced GSH, Cp, HDL levels and CAT activity. Accordingly, administration of chitosan can strengthen the antioxidant defence system of liver tissue and may decrease oxidative stress.